Effectiveness of The Family Hope Program and Non-Cash Food Assistance in West Sulawesi Province - Abbas, Risma; Haning, Mohammad Tahir; Hasniati, Hasniati; Irmawati, Irmawati; Kherunnisa, Kherunnisa; Rusdi, Muhammad; Ibrahim, Muh Akmal; T. Tikson, Deddy; Abdullah, Muh Tang (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2024)
This study aims to analyze the effectiveness and influence of the Family Hope Program and Non-Cash Food Assistance on poverty levels in West Sulawesi Province. This study used a combination of quantitative and qualitative approaches. The Family Hope Program and Non-Cash Food Assistance have been implemented effectively because they can meet food needs while increasing access to health and education services for the underprivileged. The Family Hope Program and Non-Cash Food Assistance significantly influence poverty levels in West Sulawesi Province. The results of the correlation test between the number of beneficiaries and the total budget on the poverty level produced values of -0.53 and -0.741, indicating that increasing the number of beneficiaries and the total budget in the Family Hope Program and Non-Cash Food Assistance can reduce poverty rates in West Sulawesi Province.